2021
DOI: 10.3389/fpsyt.2021.633230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Pandemic (COVID-19) Lockdown on Mental Health and Well-Being in the United Arab Emirates

Abstract: United Arab Emirates (UAE) has taken unprecedented precautionary measures including complete lockdowns against COVID-19 to control its spread and ensure the well-being of individuals. This study investigated the impact of COVID-19 and societal lockdown measures on the mental health of adults in the UAE. A cross-sectional study was conducted using an English and Arabic online questionnaire between May and June 2020. The psychological impact was assessed by the Impact of Event Scale-Revised (IES-R), and the soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
4
26
3
Order By: Relevance
“…On the contrary, Saqlain et al's (21) findings showed that Pakistani healthcare workers had good knowledge (93.2%, n = 386), positive attitude (8.43 ± 1.78), and good practices (88.7%, n = 367) regarding SARS-COV-2. Similar findings by Giao et al (22) illustrated that the majority of participants among healthcare workers in Vietnam held good knowledge and good attitude toward SARS-COV-2. More research is needed to investigate healthcare workers' competences and the knowledge necessary for their work in this challenging pandemic environment.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…On the contrary, Saqlain et al's (21) findings showed that Pakistani healthcare workers had good knowledge (93.2%, n = 386), positive attitude (8.43 ± 1.78), and good practices (88.7%, n = 367) regarding SARS-COV-2. Similar findings by Giao et al (22) illustrated that the majority of participants among healthcare workers in Vietnam held good knowledge and good attitude toward SARS-COV-2. More research is needed to investigate healthcare workers' competences and the knowledge necessary for their work in this challenging pandemic environment.…”
Section: Discussionsupporting
confidence: 84%
“…Age of the particepnts might be affected by the mean by which the questionnaire was distributed since most of social media users are young adults. Overrepresentation by female sex and young populations is found as well in other online-based studies and worth investigating with regards to casuses and its influence on results ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Most of the respondents did not dispose empty shopping bags and disinfect food packaging, a similar pattern was observed in Jordanian participants where only 15.2% of the reported disposing of all boxes, packages, and covers of food while 13.4% reported always disinfecting food packaging prior to home storage (10). In contrast, about 40% of the consumers in Indonesia and Malaysia washed or wiped food jars and cans before using them (33), and 71.9% of United Arab Emirates residents sanitized or cleaned groceries before storing them (41). A higher percentage of our participants have insufficient knowledge on the proper use of reusable kitchen sponges as they reported using them for multiple purposes such as dishes and sink.…”
Section: Discussionmentioning
confidence: 68%
“…Data from the current study revealed a significant increase in the percentage of participants experiencing exhaustion, irritability, and tension during the pandemic. Similarly in the United Arab Emirates, participants felt horrified, apprehensive, or helpless due to the COVID-19 pandemic (62). In Lebanon, citizens reported an increase in Post-traumatic Stress Disorder (PTSD) symptomatology during the second week of the COVID-19 lockdown (63) and higher fear of COVID-19, anger, and anxiety in almost half of the participants (64).…”
Section: Discussionmentioning
confidence: 99%